Outcome of laser Treatment for Retinopathy of Prematurity - Budu; Panggalo, Idayani; Muhidin, Habibah S; Ichsan, Andi Muhammad; Suryanita, Andi; Windy , Dyah Ayu (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesRetinopathy of prematurity is a proliferative disorder that requires urgent treatment. Proper casefinding and treatment will prevent permanent blindness in infants. Laser photocoagulation is anpreferred technique for the treatment of ROP. Aim of this study to describe the result of laserindirect Ophthalmoscopy in Makassar, South Sulawesi, Indonesia. MethodsThis is Observational retrospective study, from 1130 screening procedures during 2020 until 2022.This study found 41 ROP patients who had received therapy. ResultsFrom 43 patients who received therapy, most were ROP stage 3 (80%), APROP (19%) and the restwere Stage IV A . 40 infants received lasers photocoagulation, and one infant received both laserphotocoagulation and intravitreal anti-VEGF. Regression was found in all cases of stage 3 ROP.Patients with aggressive posterior ROP also were treated successfully, except one patientprogressed to stage 4 ROP. Conclusionwith screening and prompt treatment, good outcomes have been obtained for infants with ROP